ChemInform Abstract: Asymmetric Synthesis and Catalytic Activity of 3‐Methyl‐β‐proline in Enantioselective anti‐Mannich‐Type Reactions. Issue 49 (3rd December 2013) - Nagata, Kazuhiro; Kuga, Yasushi; Higashi, Akinori; Kinoshita, Atsushi; Kanemitsu, Takuya; Miyazaki, Michiko; Itoh, Takashi
Abstract Chiral β‐prolines are synthesized and used as organocatalysts in the anti‐selective Mannich‐type reaction of ketones/aldehydes with ethyl glyoxylate imine.